2007
DOI: 10.1016/j.jacc.2007.01.087
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention of Functionally Nonsignificant Stenosis

Abstract: Five-year outcome after deferral of PCI of an intermediate coronary stenosis based on FFR >/=0.75 is excellent. The risk of cardiac death or myocardial infarction related to this stenosis is <1% per year and not decreased by stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
636
0
22

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,378 publications
(686 citation statements)
references
References 44 publications
7
636
0
22
Order By: Relevance
“…FFR and CFR are both well‐validated physiological indices for guiding PCI indication 2, 3, 4, 11. A recent study also suggested that FFR measured after PCI has prognostic value, with an inverse relationship to subsequent clinical events 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FFR and CFR are both well‐validated physiological indices for guiding PCI indication 2, 3, 4, 11. A recent study also suggested that FFR measured after PCI has prognostic value, with an inverse relationship to subsequent clinical events 5.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional flow reserve (FFR) is the standard in decision making for revascularization in the catheter laboratory and has become a part of the clinical guidelines for assessing the physiological significance of epicardial coronary stenosis based on a sound concept and randomized clinical trials 1, 2, 3, 4. A recent study also suggested that FFR measured after percutaneous coronary intervention (PCI) has prognostic value, with an inverse relationship to subsequent clinical events 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cumulative evidence suggests that angiographically determined anatomical stenosis severity often underestimates or overestimates the functional significance of lesions 5, 6, 7. Fractional flow reserve (FFR) is currently the standard for decision‐making regarding revascularization in the catheter laboratory and has become part of the clinical guidelines for the assessment of the physiological significance of epicardial coronary stenosis based on sound concepts and randomized clinical trials 8, 9, 10, 11. However, FFR evaluation is still underutilized; instead, coronary angiography is widely used as a gatekeeper for decision‐making of revascularization even in large clinical trials 2, 12.…”
Section: Introductionmentioning
confidence: 99%
“…cSE‐WMP results might be useful for the decision to revascularize or not, similar to what fractional flow reserve (FFR) studies have recently proposed 26, 27, 28. Our findings point in the same direction to what has been observed with invasive FFR; such multicenter studies prospectively demonstrated that FFR is prognostically useful to proceed to revascularization, but in patients already selected to undergo diagnostic coronary angiography, although they fell short of demonstrating a benefit regarding hard events, death and MI, since in the FAME 2 study (Fractional Flow Reserve Versus Angiography for Multivessel Evaluation) the FFR‐guided percutaneous coronary revascularization arm was favored on comparison of the primary composite end point of death, MI, and target vessel revascularization, but such finding was driven by urgent target vessel revascularization 28, 29.…”
Section: Discussionmentioning
confidence: 58%